The effect of Tai Chi on glycemic control in type 2 diabetes mellitus: a meta-analysis of randomized controlled trials - Sun, Yawei; Li, Quanzhi; Xue, Weiqi (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to investigate the effects of Tai Chi on fasting blood glucose (FBG), HbA1c, blood lipids, blood pressure, and inflammatory markers in patients with type 2 diabetes mellitus (T2DM) through a meta-analysis.MethodsWe systematically searched PubMed, Cochrane Library, CNKI, CBM, WanFang, Web of Science, and Embase databases for randomized controlled trials (RCTs) evaluating Tai Chi interventions in T2DM patients. Statistical analyses were performed using Review Manager 5.4 software with random-effects models.ResultsCompared to the control group, Tai Chi significantly reduced: FBG(SMD= -0.57, 95% CI [-0.92,-0.23], P =0.001), HbA1c(MD=-0.73, 95%CI[-0.98, -0.49], P<0.00001), TG(SMD=-0.50, 95%CI[-0.91, -0.09], P =0.02), LDL-C(SMD=-0.70, 95%CI[-1.26, -0.15], P =0.01), hs-CRP(SMD=-0.71, 95%CI[-1.10, -0.31], P =0.0005), IL-6(SMD=-2.11, 95%CI[-2.88, -1.34], P<0.00001), TNF-α(SMD=-3.25, 95%CI[-3.25, -0.53], P =0.006). Subgroup analyses indicated optimal FBG reduction with: The standardized 24-form Tai Chi routine; Interventions ≥12 weeks in duration; Exercise frequency >5 sessions/week; Daily exercise duration ≥60 minutes.ConclusionTai Chi demonstrates clinically meaningful benefits for T2DM management. Future RCTs should explore age-specific (e.g., pediatric vs. geriatric) and sex-stratified responses to inform personalized exercise prescriptions.